MORTALITY INCIDENCE OF SYSTEMIC LUPUS ERYTHEMATOSUS IN DR. SOETOMO GENERAL HOSPITAL SURABAYA - Bulan Ghafirah; Yuliasih Yuliasih; Bendrong Moediarso (Universitas Airlangga, 2022)
Introduction: Systemic Lupus Erythematosus (SLE) is a chronic systemic autoimmune disorder involving a multi-organ system. Fatal autoimmune causes usually characterize SLE with a high mortality rate. In 2012 the mortality rate of SLE in Dr. Soetomo General Hospital Surabaya was 22.9%. Recently covered data hasn’t been published. Methods: This study is a descriptive retrospective. The aim is to evaluate the mortality rate using the medical records of SLE patients. All SLE patients were admitted to Dr. Soetomo General Hospital Surabaya from May 2016 to May 2017. Patients’ characteristics, disease activity, and causes of death are collected. Results: There are a total of 176 patients, with 93.2 % female, with a mean age of 29.5 and a mean duration of illness of 20 months. There were 39 deaths (22.2%), with the leading causes being a respiratory failure (33.3%), septic shock (28.2%), and undetermined (23.1%). Low levels of C3 (69.2%)andC4(69.2%)are the most common immunology profile in deed patients. The therapy used the most is the corticosteroid pulse dose(46.2%). Conclusion: It concludes that the decrease in the mortality rate of SLE in Dr. Soetomo General Hospital, Surabaya is 0.7% from 2012 to 2017.